Does Trust Mediation Benefits And Risk Consumer Perceptions Increase E-Commerce Buying Intention - rizal Ula Ananta Fauzi (Cita Konsultindo Research Center, 2021)
The development of increasingly advanced technology provides convenience to support activities for humans. Technology has changed the behavior of consumers from traditional transaction activities to online transactions because of the benefits and convenience offered. However, technology is inseparable from the risks that occur. The purpose of this study is to look at the effect of Consumers Perceived Benefits and consumers' perceived risks on online purchase intentions both directly and mediated trust. The method in this study uses path analysis with 170 respondent research samples. The findings obtained show that trust has a positive effect on purchase intentions. Consumers Perceived Benefits has a positive effect on purchase intentions both directly and mediated trust. While consumers perceived Risks negatively affect purchase intentions both directly and mediated trust. The implementation of this research is to attract consumers' online purchase intentions so the company must be able to provide confidence to consumers in the products it sells, both in terms of the benefits obtained and minimize the risks that occur.